"The Nineteen-Seventies": Summary for Presentation to The Accident Compensation Symposium - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2003)
After the Woodhouse Commission delivered its Report, more conventional political considerations surrounded its progress toward legislative enactment. The stunning replacement of common law stood at the core of reform, but the nature of the alternative scheme remained open to debate. It took six years, multiple cabinet reports and committee procedures, and political compromises amidst a change in government before the legislation took effect in 1974. In this article, one of the central players from this period reflects on the political environment leading up to enactment, and describes how the ultimate legislation modified aspects of the original Woodhouse vision.